The Role of Selected Folk Tales on Iraqi Fourth Primary Pupils’ Vocabulary Development from EFL Teachers’ Perspectives - et. al., Shahad Ismail Ibrahim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim off the study isThe Role of Selected Folk Tales on Iraqi Fourth Primary Pupils' Vocabulary Development from EFL Teachers' Perspectives.The study involvedChoose a descriptive sample was selected a random sample from a group of teachers in Babylon the researcher selected 60 schoolsin Babil Province in the 2020/ 2021 academic year. For the purpose of the interventions activities were designated to develop vocabulary from folk tales. The task preparation was rooted in a language based approach and socio-cultural language learning theory.Thus the aim of this study was to exploreValuable use of folklore education in developing vocabulary.The students' vocabulary performance was examined by explaining anecdotes. To obtain teachers' opinion on the role of stories in teaching and developing vocabulary, questionnaires were conducted on the teachers in the descriptive group.For a similar purpose, I conducted semi-structured interviews with randomly selected teachers in Babel Governorate. The data collected was analyzed through the vocabulary tests using SPSS software.The main results of the study showed that folk tales and short stories play an important role in developing vocabulary among fourth grade students.This paper aims to establish whether or not the use of Folktale texts can improve vocabulary development for fourth-graders. It also assumes pedagogical suggestions or study implications for developing vocabulary.The researcher focuses her research on English vocabulary item especially nouns, verbs, and adjectives in the selected folktale texts. To support this, simple and easy stories are chosen to be presented to the students. From the third items above the researcher want to testing about the vocabulary mastery from pronouncing, spelling and meaning.